Project-Based Learning in English for Specific Purposes (ESP): A Study of Midwifery Students and Lecturers at a Higher Education Institution in Jambi - Rahmah Rahmah; Urip Sulistyo; Marzul Hidayat; Eddy Haryanto; Mila Darmi (Media Akademika Publisher, 2025)
This study aimed to explain and describe the implementation and possible breakthrough of students centered learning approach using PjBL in English for specific purposes among midwifery students. Descriptive qualitative study was used as a method of this study. There were 11 participants consisting midwifery students and English lecturers Higher Education Institution in Jambi. The data were collected through several techniques namely documents, observation and interview. The results indicated that there are three things that must be prepared by the lecturers before implementing PjBL in the classroom; 1) lesson plan, 2) Syntax PjBL, 3) preparing questions that can foster students' critical thinking. The results of the study also reveal that the implementation of PjBL in speaking skills among midwifery students includes several steps in it namely; starting project, developing project, implementing project and evaluation. However, from the findings it was found that, there was 1 lecturer who was less intensive in implementing these stages. The findings in this study also explored and found positive perceptions of midwifery students towards implementing PjBL to enhance students' speaking skills. From the findings, the students explained that PjBL helped them to be more active, enjoy and be able to learn collaboratively. Several participants also explained that there was an increase in progress from the speaking aspect that they felt after the PjBL was implemented. In addition to a positive perspective, this study also managed to find a number of challenges that students felt while participating in learning English speaking class using PjBL. Several possible breakthroughs to the best implement of PjBL for further class were also found in this study. some recommendations and considerations regarding PjBL implementation to enhance students' speaking skills were also given